Chromosome evolution in bees - Robin E. Owen (Frontiers in Bee Science)
Of the about 1850 species of Hymenoptera for which chromosome counts are known, only just over 200 of these are bees (Apoidea). Haploid numbers (n) range from 3-28, which probably does represent the true range of chromosome numbers in this superfamily. The modal number is 17, with another peak at n=9, representing a clade of meliponid bees which has been well studied. Although much is known about the chromosomes of bees there is still much to learn about overall trends in haploid number and chromosome organization. We are still lacking this information for many important families of bees. The only andrenid bee karyotyped, Andrena togashii has the low n of 3, so we certainly need to know which other species in this family have low chromosome numbers to see if this is an exception and to further test the Minimum Interaction Theory (MIT) of Imai and colleagues which predicts the evolutionary increase in chromosome number. In general, an overall increase from low numbers (n=3-8) to the higher numbers found in the Apidae, Colletidae, Halictidae, and Megachilidae (modal numbers 17, 16, 16, 16, respectively) does appear to be followed. However, within groups this is not always the case; the Meliponid clade with n=9 being an example. The potential adaptive value of chromosome number per se is of great interest. I propose a hypothesis to account for the high (n=25) chromosome number found in the social parasitic bumble bee subgenus Psithyrus. More sophisticated techniques beyond chromosome counting and karyotyping using C-banding, will yield much more detailed information about chromosomal rearrangements as shown by the work on the neotropical meliponid bees by the Brazilian cytogeneticists, and when these are applied to other taxa of bees will undoubtedly reveal features of great interest. Genomic approaches are starting to identify chromosomal rearrangements such as inversions and this holds much potential to explore their adaptive significance.